Finite element modelling and analysis of typical "scissors-type" mechanisms - Kuan, Yonuice Yue Min (Nanyang Technological University, 2021)
A variety of mechanisms are employed in the field of engineering to make systems and processes more efficient. The scissors mechanism is one of such examples. The versatility of the scissors mechanism can be seen from its various uses, from platform lifts [1], to the construction of deployable bridges [2]. As the application of the scissors mechanism becomes more widespread, it is imperative that analyses be conducted accurately so that the structure is properly understood. The reliability of the mechanism can then be increased and the structure better utilised. In this project, the load limit and free vibration of scissors structures of various heights in the vertical configuration were studied. A scissors structure with 10 pairs of links was first modelled using ANSYS Mechanical APDL, before being subjected to different loading and boundary conditions, and analysed using the Finite Element Method (FEM). The stresses induced in the structure were studied to determine the load that causes failure. Similar static analyses were conducted for scissors structures with varying heights. Next, the free vibration of the structure was studied. It was observed that the natural frequencies of the structure decreased as the height of the structure increased. Lastly, the failure of the structure due to self-weight was studied to determine to maximum allowable height that can be formed from a scissors link of fixed dimensions.